pH sensing and regulation in cancer - Damaghi, Mehdi; Wojtkowiak, Jonathan W.; Gillies, Robert J. (Frontiers in Physiology, 2013)
Cells maintain intracellular pH (pHi) within a narrow range (7.1-7.2) by controlling membrane proton pumps and transporters whose activity is set by intra-cytoplasmic pH sensors. These sensors have the ability to recognize and induce cellular responses to maintain the intracellular pH, often at the expense of acidifying the extracellular pH. In turn, extracellular acidification impacts cells via specific acid-sensing ion channels (ASICs) and proton-sensing G-protein coupled receptors (GPCRs). In this review, we will discuss some of the major players in proton sensing at the plasma membrane and their downstream consequences in cancer cells and how these pH-mediated changes affect processes such as migration and metastasis. The complex mechanisms by which they transduce acid pH signals to the cytoplasm and nucleus are not well understood. However, there is evidence that expression of proton-sensing GPCRs such as GPR4, TDAG8, and OGR1 can regulate aspects of tumorigenesis and invasion, including colfilin and talin regulated actin (de-)polymerization. Major mechanisms for maintenance of pHi homeostasis include monocarboxylate, bicarbonate and proton transporters. Notably, there is little evidence suggesting a link between their activities and those of the extracellular H+-sensors, suggesting a mechanistic disconnect between intra- and extra-cellular pH. Understanding the mechanisms of pH sensing and regulation may lead to novel and informed therapeutic strategies that can target acidosis, a common physical hallmark of solid tumors.